High proliferation rate and TNM stage but not histomorphological subtype are independent prognostic markers for overall survival in papillary renal cell carcinoma - Polifka, Iris; Agaimy, Abbas; Herrmann, Edwin; Spath, Verena; Trojan, Lutz; Stoeckle, Michael; Becker, Frank; Stroebel, Philipp; Muelfing, Christian; Schrader, Andres J.; Barth, Peter; Staehler, Michael; et al. (Human Pathology, 2019)
Papillary renal cell carcinoma (PRCC) is currently divided in 2 subtypes. We reviewed a large cohort of PRCC and correlated subtype, morphological features and diagnostic marker expression with overall survival (OS) to uncover differences between the 2 subtypes. Three hundred seventy-six renal tumors initially diagnosed as PRCC with clinical and survival data were collected from the participating centers. Two hundred forty-six tumors were classified as PRCC1 (65.4%) and 130 as PRCC2 (34.6%) and graded according to the 2016 World Health Organization/Intemational Society of Urological Pathology grading system. Morphological features (abundant cytoplasm, necrosis, fibrous stroma, foamy macrophages and psammoma bodies) were noted. Immunohistochemical stains (MIB1, p53, Racemase, EMA, CK7, CK20, E-Cadherin) were performed using tissue microarrays. chi(2)-Tests, log-rank tests and uni- and multivariate Cox regression analysis were performed. Both subtypes displayed different morphological features and immunohistochemical profiles: abundant cytoplasm was more frequent in PRCC2, while foamy macrophages were more common in PRCC1. Abundant cytoplasm and presence of psammoma bodies were associated with poorer OS. PRCC1 showed more frequent CK7 expression, PRCC2 more frequent E-Cadherin, p53 and higher MIB1 expression (>15%). Expression of Racemase and CK7 was associated with better OS, while high MIB1 (>15%) was associated with poorer OS. In multivariate analysis, the only independent predictors of OS were proliferation (MIB1), tumor stage, metastasis and age at surgery. Subtype was not an independent prognostic factor. Therefore, PRCC subtype on its own is not suitable for estimating survival. More data focusing on PRCC tumor biology is needed to define prognostic subgroups, especially in PRCC2. (C) 2018 Elsevier Inc. All rights reserved.
CRIS-Team WoS Importer:2019-03-06